STRATEGI HEDGING DALAM KEBIJAKAN LARANGAN EKSPOR NIKEL DI INDONESIA - Amelia Zahara Mulya; Rizal Budi Santoso (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze how Indonesia’s nickel ore export ban and smelter investment regulation function as a national economic hedging strategy in dealing with global commodity price fluctuations and international trade uncertainties. The research applies a descriptive qualitative approach using secondary data from Statistics Indonesia (BPS), the Ministry of Energy and Mineral Resources, BKPM, TradeMap, government regulatory documents, and relevant literature.The findings show that the downstreaming policy successfully shifted Indonesia’s export structure from primary commodities to higher value-added products such as ferronickel, Nickel Pig Iron, stainless steel, and battery-related materials. Smelter investment regulation also strengthens supply chain integration, increases domestic industrial capacity, broadens market coverage, and enhances income stability through medium- to long-term trade arrangements. Therefore, downstreaming policy and investment regulation serve as an effective non-financial hedging strategy that increases value added, economic resilience, and Indonesia’s bargaining power in global trade.